Prevalence and trends of overweight and obesity in older adults from 10 European countries from 2005 to 2013 - Peralta, M.; Ramos, M.; Lipert, A.; Martins, J.; Marques, A. (Scandinavian Journal of Public Health, 2018)
Overweight and obesity are clinical public health concerns worldwide. Among older adults, the prevalence of overweight and obesity is considered high. The purpose of this study was to provide current data regarding the prevalence and trends of overweight and obesity of adults, from 2005 to 2013, in 10 European countries. Methods: The data used in the present study was derived from the first, second, fourth and fifth waves of the Survey of Health, Ageing and Retirement in Europe (SHARE). The present study includes individuals aged ≥ 50 years from 10 European countries. Body mass index (BMI) was calculated from self reported height and weight (kg/m2). Results: More than half of the participants were overweight or obese (BMI≥25). Between 2005 and 2013 the general prevalence of overweight (BMI≥25 kg/m2) was slightly above 60%. The prevalence of overweight or obesity was relatively stable between 2005 (60.1%, 95% CI: 59.3%, 60.9%) and 2013 (60.3%, 95% CI: 59.7%, 60.9%). Obesity (BMI≥30) prevalence increased significantly (1.6%, 95% CI: 0.7%, 2.6%), from 17.5% in 2005 to 19.2% in 2013. In most countries there is an increase of the prevalence of obesity, but the only significant increase was observed in Germany (5.8%, 95% CI: 1.8%, 9.9%). In Spain the prevalence of obesity decreased significantly between 2005 and 2013 (-4.7%, 95% CI: -8.8%, -0.5%). Conclusion: This study findings indicate that the prevalence of overweight among elderly Europeans is relatively stable, but the number of obese people is rising.